PHYSICIAN’S CHALLENGES IN THE RELATIONSHIP WITH THE PATIENT AND HIS WORK: HUMANIZING THOSE WHO ARE DEHUMANIZED - Lúcio Sátiro Maia Pinheiro, Francisco (Health and Society, 2023)
Doctors and other health professionals have gained wide prominence in society since the dawn of civilization. However, with the COVID-19 pandemic, the whole society has noticed the wide importance of the work of doctors, nurses and other health professionals. In this aspect, it is valuable to discuss the relationship between physician and patient and the aspects that impact on this issue. Thus, the general objective of this work is to analyze the variables and considerable aspects existing in the relationship between physician and patient and the existing challenges. The research methodology used was qualitative research. Thus, data collection was performed with bibliographic research in national databases. This work concludes with the premise that there are several challenges in the relationship between doctor and patient, among these as the patients and difficult families, the long working hours and precarious working conditions, the disregard of the humanity of the doctor and his consideration as a kind of machine and not as a professional who is, above all, a human being.